Preparation and Application of Dual-Crosslinked Highly Elastic Aerogel Dressing - Jensen, Lasse; Park, Peter; Arellano, Carlos (Journal of Functional Materials and Applied Engineering, 2024)
Medical dressings are critical materials for wound care, effectively promoting wound healing and alleviating patient suffering. With social development and improved living standards, higher functional requirements for medical dressings have emerged. In areas such as sensitive wound care and cavity bleeding, elastic and expandable dressings play vital roles. Aerogel dressings, characterized by their three-dimensional porous structure, low density, high porosity, and high specific surface area, offer significant advantages. Currently, polyurethane aerogels are the most commonly used functional aerogel dressings. However, their preparation heavily relies on petroleum-derived chemicals such as methylene diphenyl diisocyanate and toluene diisocyanate, resulting in high production costs, high prices, and poor degradability, which limit their widespread application. Natural polymers, as important biomass materials, offer advantages such as wide availability, excellent biocompatibility, and soil degradability. Amidst increasing petroleum resource shortages and environmental concerns, it is urgent to develop natural polymer aerogel dressings with tailored structures and properties to achieve green iterative upgrades of functional aerogel dressings. This study utilizes sodium carboxymethyl cellulose (CMC), hydroxypropyl cellulose (HPC), and coniferous pulp (CP) as raw materials. Through dual physical and chemical crosslinking strategies, combined with ice-templating, pore-forming agents, and foaming agents, a multi-level porous structure was constructed to prepare CMC-HPC dual-crosslinked highly elastic aerogel dressings. The structure and properties of the resulting aerogel dressings were tested and analyzed. The results indicate that heating promotes the ring-opening of epichlorohydrin (ECH), enabling covalent bonding with CMC to achieve chemical crosslinking. The introduction of HCl creates an acidic environment, protonating the sodium carboxylate groups of CMC into carboxyl groups, followed by freezing to facilitate hydrogen bonding for physical crosslinking. Under the synergistic effects of ice-templating and the pore-forming agent HPC, washing and freeze-drying yielded CMC-HPC aerogel dressings with a hierarchical porous structure. Post-treatment with a plasticizer partially offset the hydrogen bonding interactions between CMC molecular chains, improving the elastic properties of the aerogel dressings. The CMC-HPC dual-crosslinked aerogel dressings maintained their initial shape after 24 hours of immersion in deionized water, exhibiting minimal swelling. Compared to gelatin sponges and medical gauze, the aerogel dressings demonstrated excellent in vitro cytocompatibility, indicating their promising application potential and practical value as wound dressings.